2022
DOI: 10.1111/jopr.13476
|View full text |Cite
|
Sign up to set email alerts
|

Additively Manufactured Surgical Implant Guides: A Review

Abstract: Static computer assisted implant surgery (s-CAIS) is an integral part of the digital workflow in implant dentistry and provides the link between the virtual planning environment and surgical field. The accuracy of s-CAIS is influenced by many cumulative factors including the fit of the template which is related to the manufacturing process. This critical review provides an overview of the current research on additively manufactured surgical implant guides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…A variety of methods for creating such 3D-printed surgical guides have evolved over time. FFF uses a melted thermoplastic extruded by the printer head, which is continuously layered on a platform, while in the material jetting process, a carriage jets photopolymers onto a surface, which are then cured with ultraviolet light[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of methods for creating such 3D-printed surgical guides have evolved over time. FFF uses a melted thermoplastic extruded by the printer head, which is continuously layered on a platform, while in the material jetting process, a carriage jets photopolymers onto a surface, which are then cured with ultraviolet light[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Computer-assisted implant surgery sets the link between virtual planning and surgery, and a digitally planned implant placement has been shown to be significantly more accurate than freehand placement. A high level of accuracy of the surgical guide is needed for the protection of vital structures and a better interaction between the surgeon and the prosthodontist[ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, pilot-drill guidance offered the advantage of improved implant deviation compared to the freehand approach. However, it was still prone to a large angular deviation which could have resulted due to an undesirable mechanical tolerance between the drills and sleeve or accumulative error at the data acquisition, software processing and template manufacturing steps of the digital workflow [ 19 ]. In addition, the findings suggested that experienced practitioners offered higher angular deviation compared to novice practitioners with all the approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The production of guides involves multiple, closely-linked steps, including data collection and integration, design of the implanting plan and guide structure, and manufacturing, and errors in previous steps will accumulate in the final guides (Putra et al, 2022;Rouzé L'Alzit et al, 2022). Factors influencing template accuracy can be roughly divided into three categories: 1) System error: that is, errors generated during CBCT scanning and data conversion, which cannot be controlled by humans; 2) Manufacturing error: related to the type of 3D printer (Zhang et al, 2022) (Table 1), selection of printing materials, use of supporting structures, slicing method and software types (Cho et al, 2021;Elliott et al, 2022;Rubayo, et al, 2021); and 3) Other factors.…”
Section: Research Status On Additive Manufacturing Applications In Im...mentioning
confidence: 99%